PSYCHOSOCIAL DETERMINANTS OF PHYSICAL ACTIVITY AMONG ADOLESCENTS AT SMAN 1 MATARAM: PERCEPTION, SELF-EFFICACY, AND CUES TO ACTION - Juliantini, Ni Putu Liska; Anulus, Ayu; S., Aulia Mahdaniyati; Pebruanto, Henry (International Journal of Health Science & Medical Research, 2026)
Physical activity among adolescents plays an important role in maintaining health and preventing future health problems. However, adolescents’ levels of physical activity still tend to vary and are influenced by psychosocial factors. The novelty of this study lies in the comprehensive application of the Health Belief Model to analyse factors related to physical activity in high school students in Mataram City. The purpose of this study was to determine the relationships among the Health Belief Model constructs (perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and cues to action) and students’ levels of physical activity at SMAN 1 Mataram City. The research used an observational-analytical design with a cross-sectional approach, involving 310 respondents selected via a total sampling technique, and analyzed the data using the Spearman correlation test. The results showed that perceived susceptibility, perceived severity, and perceived benefits were not significantly related to physical activity, while perceived barriers (rs = −0,25; P-value 0,001), self-efficacy (rs = 0,12; P-value = 0,029), and cues to action (rs = 0,11; P-value = 0,041) had a significant relationship with physical activity, although weak. The conclusion of this study shows that psychosocial factors, especially perceived barriers, self-efficacy, and motivation to act, play a greater role in influencing adolescent physical activity than perceived risks and benefits, so that interventions to increase physical activity in schools need to focus on strengthening self-efficacy, increasing cues to action, and reducing barriers perceived by students.